â€œJAGONGANâ€ SEBAGAI BENTUK KOMUNIKASI SOSIAL PADA MASYARAKAT SOLO DAN MANFAATNYA BAGI PEMBANGUNAN DAERAH - Nawiroh Vera; Doddy Wihardi (Jurnal Ilmiah Komunikasi Makna, 2012)
Communication can be performed directly (orally) or with the media. In the current de- velopment of communication technology, the use of modern mass media such as the Internet is very popular. ICT era was allegedly able to change traditional forms of communication that is widely available in Indonesia. Traditional media is part of social communication, in Indonesia many types of traditional media are still often used in conveying the message, idea, or opinion. Traditional media are in the form of folk art as well as in the form of verbal communication are usually done in groups in certain areas. In the city there are cultural Solo Jagongan, ie talking together while relaxing. Jagongan can occur in a coffee shop, pos kamling, wedding ceremony, or in the stalls. Usually the people (men) hang out and talk and stay up until morning. Women also do the same thing but usually done during the day. The term jagongan so entrenched in the community in the city of Solo. Type of social communication should be used as a means of developing in Indonesia. Many communities in other regions who have ways of communicating with the group. As the local culture such patterns can be used to disseminate a variety of inno- vations, government policies, and others. Based on this background, the authors are interested to know the extent of social communication such as jagongan role in development in the city of Solo? Methods used are observation and interviewing informants. Purposive sampling tech- niques and qualitative data were analyzed descriptively.